2023
DOI: 10.3390/jrfm16020122
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fintech and Digital Financial Services on Financial Inclusion in India

Abstract: India’s financial inclusion has significantly improved during the last several years. In recent years, there has been a rise in the number of Indians who have bank accounts, with this figure believed to be close to 80% at present. Fintech businesses in India are progressively becoming more noticeable as the Government of India (GoI) continues to strive for expanding financial services to the underbanked sector of the population. To reach the underbanked segments of the population and provide a stable operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…A poll by Allo (2021) of 424 institutions worldwide revealed that the Covid 19 pandemic crisis has had an impact on education and that online learning is essential for carrying out educational activities (Suresh, Priya, & Gayathri, 2018). Teachers must be able to adjust to changes in technology in the educational process and use elearning to transfer information (Sun, Tang, & Zuo, 2020;Al Lily, el al., 2020), (Asif, M., Khan, M. N., Tiwari, S., Wani, S. K., & Alam, F. (2023).…”
Section: Literature Surveymentioning
confidence: 99%
“…A poll by Allo (2021) of 424 institutions worldwide revealed that the Covid 19 pandemic crisis has had an impact on education and that online learning is essential for carrying out educational activities (Suresh, Priya, & Gayathri, 2018). Teachers must be able to adjust to changes in technology in the educational process and use elearning to transfer information (Sun, Tang, & Zuo, 2020;Al Lily, el al., 2020), (Asif, M., Khan, M. N., Tiwari, S., Wani, S. K., & Alam, F. (2023).…”
Section: Literature Surveymentioning
confidence: 99%
“…The research shows that enterprises and firms may improve performance by adopting flexible digitalization and human capital strategies. Financial inclusion and the proliferation of Fintech companies in India are the subjects of Asif et al [ 22 ]. Based on these results, it is clear that providing financial services to underbanked sectors is crucial to achieving the goal of full financial inclusion, especially for the middle class.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 'people dimension' in TBL reporting pertains to the social facets of sustainability, encompassing matters like employee well-being, community involvement, and human rights. By considering elements such as ethical labour practices, diversity and inclusivity, and charitable initiatives, organizations can showcase their dedication to fostering a beneficial social influence (Asif et al, 2023). Stakeholders, which include employees, customers, and local communities, anticipate that businesses will play a role in enhancing social welfare beyond solely generating profits.…”
Section: Introductionmentioning
confidence: 99%